Trends in abortion services and sociodemographic profile of women those availed abortion services at Parivar Seva clinics in India - Thakur, Neelima; Chhabra, Pragti (International Journal Of Community Medicine And Public Health, 2021)
Background: Despite the law for termination of pregnancy, women continue to have illegal or unsafe abortions leading to incomplete abortions in India. The aim of the paper is to identify the trend of abortion services, clients treated for safe and incomplete abortion their client characteristics in the Parivar Seva Sanstha clinics. Methods: Retrospective analysis of the available data from 31 Parivar Seva clinics India. Retrospective study carried out in 31 clinics of the Parivar Seva Sanstha in 11 states. Data of women who were treated for medical termination of pregnancy (MTP) and other abortion between the periods of January 2018 to December 2019 was obtained from the records for analysis. Proportion of MTP and other abortion for different categories was computed and Chi square test was applied to study the association. Results: More than forty thousand women availed abortion services from the clinics every year. The frequency of incomplete abortion increased from 34.7% to 38.1% from 2018 to 2019. Young women, women of Muslim religion, higher income group, who reached the clinics from long distance, with no parity and no previous history of abortion had more probability of availing services for incomplete abortion as compared to MTP. Majority of women were seeking MTP and incomplete abortion services in their first trimester only; about two thirds (61.4% and 66%) of these had surgical abortion in first trimester. Majority (86.1% and 87.5%) of women obtained MTP services up to 12 weeks of gestation. Conclusions: There is urgent need to create awareness and educate the women regarding safe abortion, access of family planning, legality of abortion, medication outside the health facilities.